UP Mindanao course scheduler (UPMCS) subject scheduler sub-system (SSSS) - Tiempo, Algie May Orbita (2011)
The application aimed to automate the scheduling process used by the Department of Mathematics , Physics and Computer Science in scheduling the subjects having three (3 ) units offered by the department. It consisted of four modules namely : (1) the scheduler module that assigns time day and takers to the lecture and laboratory components of a subject; (2) the add, edit and delete module that allows the adding of subject into the application for scheduling, updating the subject information, and deleting the subjects that will no longer be needed to be scheduled.; (3) the save and revise module that allows the user to save the created schedule and revise it before having the final list and (4) the list creator module that generated the alpha and student list which summarizes the schedule created by the user. The application also detects three conflicts namely : (a) conflict for duplicate schedule, (b) conflict for the takers, and (c) conflict for the lecture and laboratory components. The scheduling of subjects is based on the year level of the students of the university. The application follows a certain scheduling scheme. All schedules that can be generated follow this scheme. This application would lessen the burden of the department chair in scheduling the subjects offered by the department. Since the university follows a standard scheduling scheme, this application can be applied to all departments. However, it must be further developed to cater to all the needs of the departments like offering subjects having more or less than three (3) units. Learning Ajax and thorough practice of using the Codelgniter framework are also recommended to further develop the application.